DEVELOP LINGUISTIC COMPETENCES IN FUTURE TEACHERS’ THEORETICAL ASPECTS - Kenjayeva. M. A (Scholar Express Journal, 2023)
This article provides information on the theoretical aspects of the development of linguistic competences in future teachers and the competence-based approach, the foundation and competences related to science are relevant tools in the modern world
Keywords: linguistic competence; competence-based approach; knowledge; skill